[Page 32-33] - Scale, Bernard (London: Printed for Robert Sayer, and John Bennet, 1776)
An Hibernian atlas, or, General description of the kingdom of Ireland: divided into provinces with its sub-divisions of counties, baronies, showing their boundaries, extent, soil, produce, contents, measure, members of Parliament, and number of inhabitants: also the cities, boroughs, villages, mountains, bogs, lakes, rivers and natural curiosities: together with the great and bye post roads.
An Hibernian atlas, or, General description of the kingdom of Ireland
County of Kildare.
Keywords: Ireland ?- Maps; Ireland -- Description and travel -- Early works to 1800; Ireland ?- Surveys; Ireland -- Road maps; Kildare (Ireland : County)